Exploring corporate social responsibility and financial performance through stakeholder theory in the tourism industries. (October 2017) - Theodoulidis, Babis; Diaz, David; Crotto, Federica; Rancati, Elisa
Abstract: The literature examining the relationship between corporate social responsibility (CSR) and corporate financial performance (CFP) in the tourism industries is extensive but it has not verified the relationship unambiguously. This has been attributed to the methodological artefacts used, but also to the lack of a solid theoretical foundation. Based on stakeholder theory, this paper proposes the use of two models that explicitly investigate the relationship between stakeholder management, expressed as CSR activities, firm strategy and CFP. The strategic stakeholder model and the intrinsic stakeholder commitment model are evaluated in terms of their descriptive accuracy in four different tourism-related industries (airlines, casinos, hotels and restaurants) using panel regressions for the years 2005–2014. The results provide useful theoretical insights into the way in which CSR interacts with firm strategy and CFP, as well as managerial insights into how tourism practitioners can identify which CSR activities may impact CFP. Highlights: Relationship between stakeholder management (CSR), firm strategy and CFP. Development of a sound theoretical foundation based on stakeholder theory. Strategic stakeholder and intrinsic stakeholder commitment models proposed. Evaluation in four tourism industries: airlines, casinos, hotels and restaurants. Existence of direct effects of CSR on CFP and indirect effects via firm strategy.